RELIGIOUS HARMONY AND PEACEFUL CO-EXISTENCE: A QURANIC PERSPECTIVE - Abdul Muthaliff, Mohamed Mihlar; Abd Rahman, Mohd Rosmizi; Mahyuddin, Muhammad Khairi; Mokhtar, Ahmad Najaa’; Ahmad, Yuseri (‘Abqari Journal, 2019)
Islam promotes religious harmony and peaceful co-existence not only among the Muslims, but also among the people of other faiths. As established by Islām, it is important for every Muslim to tolerate other religions, and to follow the policy of living peacefully with other nations, religions etc., despite fundamental disagreements. This article is aimed to explore how the Holy Qur᾽ān appeals to Muslims to engage in religious tolerance and harmony with the people of other religions in order to bring a true manifestation of peace and brotherhood in diversity and respect for each other’s rights on the basis of their common humanity. Hence, the article focuses on the Quranic principles for religious harmony and peaceful co-existence among the people, such as the equality of mankind, mutual understanding, cooperation, and freedom of religion and thought. The study concludes by highlighting the importance of the Quranic view of peace and coexistence which is interwoven with the universal moral discourse that unites all human beings.